Co-implementation: collaborative and concurrent approaches to advance embedded implementation in the health sciences - Archibald, Mandy M. (Frontiers in Health Services, 2023)
There is a global movement towards stakeholder engagement in healthcare research. This movement has been catalyzed by a need to create context relevant evidence of maximal utility to health service provision and policy. The concept of “co-implementation” has potential to inform and extend these discussions of partnership and to complement the growing literature on collaborative implementation. Attending to this concept may preempt conceptual confusion and provide opportunities for sustainable and context-responsive embedded research necessary for the strengthening of health systems. In this perspective article, I seek to advance the discussion of co-implementation through an examination of the concept and through consideration of it merits to the health sciences.